Development of a Safe and Effective Vaccinia Virus Oncolytic Vector WR-Δ4 with a Set of Gene Deletions on Several Viral Pathways - Ernesto Mejías-Pérez; Liliana Carreño-Fuentes; Mariano Esteban (Molecular Therapy: Oncolytics, 2018)
Despite the effectiveness of classic treatments and available diagnostic tools, cancer continues to be a leading world health problem, with devastating cancer-related death rates. Advances in oncolytic virotherapy have shown promise as potentially effective treatment options in the fight against cancer. The poxviruses have many features that make them an attractive platform for the development of oncolytic vectors, with some candidates currently in clinical trials. Here, we report the design and generation of a new oncolytic vector based on the vaccinia virus Western Reserve (WR) strain. We show that the WR-Δ4 virus, with the combined deletion of four specific viral genes that act on metabolic, proliferation, and signaling pathways (A48R, B18R, C11R, and J2R), has effective anti-tumor capabilities in vivo. In WR-Δ4-infected mice, we observed strong viral attenuation, reduced virus dissemination, and efficient tumor cell growth control in the B16F10 syngeneic melanoma model, with enhanced neutrophil migration and activation of tumor antigen-specific immune responses. This approach provides an alternative strategy toward ongoing efforts to develop an optimal oncolytic poxvirus vector. Keywords: oncolytic vectors, vaccinia virus, virotherapy, immune responses